Curriculum Development to Promote Reading Habits and Reading Literacy through Isan Local Literature for Primary School Students - Promma, Kamonlak; Saihong, Prasong; Karupan, Wannapa; Boonnakkasaen, Artith; Seehamongkon, Yannapat; Kulchit , Nippita (Journal for Developing the Social and Community, 2026)
Background and Objectives: This study aimed to develop a curriculum to promote reading habits and reading literacy through the use of Isan local literature for primary school students. The research was conducted in two phases. Phase 1 focused on drafting the curriculum based on the synthesis of curriculum components derived from the study of current conditions and needs for curriculum development. Relevant documents and research on curriculum development, reading habits, reading literacy, and Isan local literature were reviewed. Data on conditions and needs were collected from stakeholders using questionnaires and focus group discussions. The research instruments included a document analysis form, a questionnaire on conditions and needs, and an unstructured interview guide. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. Methodology: Phase 2 involved developing the curriculum and evaluating the appropriateness of the draft. Five experts in curriculum and instruction, Thai language learning management, research and statistics, and local literature participated in the curriculum critique and evaluation. The evaluation instrument was a five-point Likert scale questionnaire consisting of 11 items covering four aspects: curriculum development, learning activities, teacher instruction, and measurement and evaluation. The instrument showed acceptable content validity, with an Index of Item-Objective Congruence (IOC) ranging from 0.50 to 1.00. Data were analyzed using mean and standard deviation. Results: The developed curriculum consisted of seven components: curriculum principles, objectives, structure, learning activities, instructional media and learning resources, measurement and evaluation, and learning units. The overall evaluation indicated a high level of appropriateness (𝑥̄ = 4.39, S.D. = 0.56). Conclusion: The developed curriculum was considered appropriate in terms of structure, content, and learning management processes and can serve as a guideline for promoting reading habits and reading literacy among primary school students.